Does a job guarantee pay off? The fiscal costs of fighting long-term unemployment in Austria - Simon Theurl; Dennis Tamesberger (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
The idea of a job guarantee (JG) to tackle unemployment has become popular again over recent years. Critics often point to the fiscal costs and the macroeconomic impact of a government financing full employment. In this paper, we analyse the fiscal costs of a JG for long-term unemployed people over the age of 45 in Austria. We show that a JG pays off in the long run. Even if the amount of jobs to be provided increases in times of a recession, or if a government starts with a certain amount of jobs and increases it afterwards, the JG would pay for itself.
Keywords: J20; J23; J45; J48; J68; H50; 330; job guarantee; employer of last resort; long-term unemployment; unemployment; fullemployment; budget; finance; Austria